Pedagogical Practices in D.El.Ed. Programme of DIETs of Odisha: An Exploration - Krishnan, Dr. Dhanya; Mallick, Mr. Bijay Kumar (Voices of Teachers and Teacher Educators, 2020)
The paper tries to explore the pedagogical practices of Diploma in Elementary Education (D.El.Ed.) programme of Odisha with specific reference to foundation courses, pedagogy courses and practicum. A mixed method was used wherein convergent parallel design has been employed. By using stratified random sampling technique, six District Institutes of Education and Trainings (DIETs) were selected-two each from the three revenue divisions of Odisha. From each DIET, all student teachers who were pursuing 2nd year D.El.Ed. programme and all teacher educators available during the time of data collection were taken for the study. In total 384 student teachers and 41 teacher educators participated in the study. The pedagogical practices were classified under 3 categories-inside class room, outside classroom and institutional practices. Rating scale was administered to student teachers of DIET to understand student teachers’ perceptions on pedagogical practices. Classroom observation, Interview and Focus Group Discussion (FGD) are the other tools/techniques used in the study for data collection. Data was analysed both quantitatively and qualitatively. Frequencies and percentages were calculated and in addition, content analysis was used to analyse interview and FGD data. It was found that a majority of student teachers expressed favourable response to pedagogical practices of D.El.Ed. programme. Teachers claim that a variety of methods are used to transact the curriculum. Analysis of data revealed that though some of the postulates of National Curriculum Framework for Teacher Education (NCFTE)-2009 are reflected in the overall pedagogical practices, more efforts are required in this direction to make process based elementary teacher education available at DIETs.